A novel interval-valued neutrosophic EDAS method: prioritization of the United Nations national sustainable development goals - Karasan, Ali; Kahraman, Cengiz (SPRINGER, 2018)
Evaluation based on distance from average solution (EDAS) method is based on the distances of each alternative from the average solution with respect to each criterion. This method is similar to distance-based multi-criteria decision-making methods such as TOPSIS and VIKOR. It simplifies the calculation of distances to the deal solution and determines the final decision rapidly. EDAS method has been already extended to its ordinary fuzzy, intuitionistic fuzzy and type-2 fuzzy versions. In this paper, we extend EDAS method to its interval-valued neutrosophic version with the advantage of considering a expert's truthiness, falsity, and indeterminacy simultaneously. The proposed method has been applied to the prioritization of United Nations national sustainable development goals, and one-at-a-time sensitivity analysis is conducted to check the robustness of the given decisions. The proposed method is also compared with the intuitionistic fuzzy TOPSIS method for its validity.
Keywords: EDAS; Interval-valued neutrosophic sets; Multi-criteria; United Nations; Deneutrosophication; MULTICRITERIA DECISION-MAKING; FUZZY-SETS; ENVIRONMENT; VIKOR; Computer Science